PEMIKIRAN FEMINISME TOKOH UTAMA DALAM NOVEL PEREMPUAN BERKALUNG SORBAN KARYA ABIDAH EL KHALIQI - Rofiqul Amin (EDU-KATA, 2018)
This research aims to: Describe the idea of ​​feminism main character in the novel Perempuan Berkalung Sorban worked by Abidah el Khaliqi. This research uses descriptive interpretative method. This method is a combination of analytical methods, interperatif, and descriptive. Results of the analysis in this study is, thought the main character in the novel Women Berkalung Sorban Abidah El-Khaileqy work is always based on a perceived sense of injustice because of the differences in gender. This injustice arises because in society there is a patriarchal system that put women under men, or in other words, the male is higher than female.